THE EFFECT OF NANOPARTICLE STANDARDIZED EXTRACTS OF BAY LEAVES (Syzygium polyanthum (Wight) Walp.) IN LOWERING BLOOD GLUCOSE LEVELS OF WHITE RATS (Rattus norvegicus) - Hadiyanti Hadiyanti; Deni Rahmat; Chaidir Chaidir (Jurnal Ilmiah Farmako Bahari, 2023)
Several studies revealed that Syzygium polyanthum (Wight) Walp, known as bay leaves, has the potential to be used as herbal medicine due to its active compounds including flavonoids. Herbal medicines are chosen to replace synthetic drugs which have side effects on health. However, some active substances of herbal medicines including bay leaves are less soluble in water and have low bioavailability to be absorbed by the intestine is low. A formulation into nanoparticles will provide more effective results. This study aimed to develop a standardized herbal medicine from the bay leaves extract in nanoparticle form with fine quality and efficacious in lowering blood glucose levels. The nanoparticle formulation was conducted using the ionic gelation method with chitosan- tripolyphosphate base and was designed into pre- and post-test-controlled group designs. Wistar white rats (Rattus norvegicus) were used as the experimental animal and grouped into a negative control group, normal control group, positive control (Glibenclamide) groups, and test dosages-induced control group. Fasting blood glucose levels were measured using an enzymatic glucometer and the AUC was analyzed based on the trapezoidal formula statistically using the Kruskal-Wallis and Mann-Whitney tests. The results showed that the bay leaves contained secondary metabolite including flavonoid with concentrations at 96%, 70%, 50%, respectively. The nanoparticles sizes were 1.48%; 1.62%; 1.50%; and 0.03%, respectively. The average particle size was 549.2 nm, and the zeta potential was -40.2 mV. Nanoparticle administration at a dose of 426.80 mg/kg BW; 213.40 mg/kg BW; and 106.70 mg/kg BW showed decreasing blood glucose levels when compared to the positive control group but not significant (P>0.005). The smallest dose of nanoparticle extract that lowered blood glucose levels was at a dose of 106.70 mg/kg BW. It can be concluded the nanoparticles form of bay leaves extract can lower blood glucose levels and meets the quality requirements.